Improving Gross Motor Skills of Children Aged 5–6 Years Through Gambang Suling Dance Learning Based on YouTube Media - Uswatun Khasanah; Ezif Rizqi Imtihana (Golden Ratio of Data in Summary, 2026)
This study aims to improve the gross motor skills of children aged 5–6 years through Gambang Suling dance learning based on YouTube media. The background of this research is the low level of gross motor skills among Group B children at Tunas Ananda Kindergarten, as indicated by limited balance, coordination, and ability to follow rhythmic movements. This study employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The research subjects were 15 children. Data collection techniques included observation, interviews, and documentation, with data analyzed descriptively using quantitative percentages of learning mastery. The results showed a significant improvement in children’s gross motor skills in each cycle. The mastery percentage increased from 42% in the pre-action stage to 68% in Cycle I, and reached 87% in Cycle II. This improvement occurred because the learning process integrated dance activities involving large muscle movements, utilized YouTube as an audiovisual medium, applied playback speed features to facilitate understanding of movements, and implemented a challenge-based learning approach that enhanced children’s motivation and engagement. Thus, it can be concluded that Gambang Suling dance learning based on YouTube media is effective in improving the gross motor skills of children aged 5–6 years.